Stratospheric circulation response to large Northern Hemisphere high-latitude volcanic eruptions in a global climate model - H. Guðlaugsdóttir; H. Guðlaugsdóttir; Y. Peings; D. Zanchettin; G. Magnusdottir (Atmospheric Chemistry and Physics)
Stratospheric aerosols after major explosive volcanic eruptions can trigger climate anomalies for up to several years following such events. Whereas the mechanisms responsible for the prolonged response to volcanic surface cooling have been extensively investigated for tropical eruptions, less is known about the dynamical response to high-latitude eruptions. Here we use global climate model simulations of an idealized 6-month-long Northern Hemisphere high-latitude eruption to investigate the stratospheric circulation response during the first three post-eruption winters. Two model configurations are used, coupled with an interactive ocean and with prescribed sea-surface temperature. Our results reveal significant differences in the response of the polar stratosphere with an interactive ocean: the surface cooling is enhanced and zonal flow anomalies are stronger in the troposphere, which impacts atmospheric waveguides and upward propagation of large-scale planetary waves. We identify two competing mechanisms contributing to the post-eruption evolution of the polar vortex: (1) a local stratospheric top-down mechanism whereby increased absorption of aerosol-induced thermal radiation yields a polar vortex strengthening via thermal wind response and (2) a bottom-up mechanism whereby anomalous surface cooling yields a wave-activity flux increase that propagates into the winter stratosphere. We detect an unusually high frequency of sudden stratospheric warmings in the simulations with interactive ocean temperatures that calls for further exploration. In the coupled runs, the top-down mechanism dominates over the bottom-up mechanism in winter 1, while the bottom-up mechanism dominates in the follow-up winters.